Preparation method for in-situ preparation of monatomic electrocatalyst on surface of current collector

By using the method of preparing single-atom electrocatalysts in the electrolytic water hydrogen production equipment in the in-situ surface of the current collector, the problems of poor stability and low catalytic efficiency of the membrane electrode catalyst are solved, and efficient hydrogen production performance and long-term stability of the electrolytic water hydrogen production are achieved.

CN119571376AInactive Publication Date: 2025-03-07SUZHOU LUYUN HYDROGEN ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411758219.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the existing electrolytic water hydrogen production equipment, the bonding force between the catalyst slurry and the release film of the membrane electrode is weak, resulting in poor catalyst stability and low catalytic efficiency, and the non-conductivity of the binder increases the contact resistance inside the electrode.

Method used

The method of preparing single atomic electrocatalysts in situ on the current collector surface is adopted. By forming catalyst active sites on the current collector surface, polydopamine nanoparticles are combined with metal salts to achieve in situ pinning of the substrate, and a single atomic electrocatalyst is formed by high-temperature annealing treatment.

Benefits of technology

The stability and catalytic efficiency of single-atom electrocatalysts are improved, the interface resistance between the catalyst and the current collector is reduced, the binding force between the catalyst and the current collector is enhanced, and the long-term service life of the catalyst is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119571376A_ABST
    Figure CN119571376A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method for in-situ preparation of a monatomic electrocatalyst on the surface of a current collector, which comprises the following steps: S1, cleaning the current collector, and naturally drying; s2, preparing a metal salt solution; s3, preparing a dopamine polymerization solution, and mixing the dopamine polymerization solution with the metal salt solution obtained in S2 to obtain a precursor solution; s4, allowing the current collector treated in the step S1 to stand in the precursor solution obtained in the step S3, and heating and evaporating to obtain a catalyst rough blank; and S5, carrying out annealing treatment on the catalyst rough blank obtained in the step S4 to obtain the monatomic electrocatalyst. The monatomic electrocatalyst prepared by the preparation method for in-situ preparation of the monatomic electrocatalyst on the surface of the current collector is distributed on the surface of the current collector, so that the monatomic electrocatalyst can be prevented from falling off or being inactivated in a long-term use process, and the long-term service stability of the monatomic electrocatalyst can be remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of hydrogen production by electrolysis of water, and in particular to a method for preparing a single-atom electrocatalyst in situ on the surface of a current collector. Background Art

[0002] Water electrolysis is a clean way to produce energy by using renewable energy (such as solar or wind power) to provide electricity to decompose water into hydrogen and oxygen. By electrolyzing water to produce hydrogen, electrical energy can be converted into hydrogen, which can then be stored. This method can solve the intermittent problem of renewable energy, because hydrogen can be converted into electricity when needed, achieving a smooth supply of energy.

[0003] At present, membrane electrode is an important component in water electrolysis hydrogen production equipment. It mainly provides catalytic effect. The membrane electrode is mainly composed of release film and catalyst slurry. The prepared catalyst slurry needs to be coated on the release film and solidified on the surface of the release film through a binder to form a catalyst layer. However, the membrane electrode material prepared by this method often has two significant problems. First, the binder is non-conductive, which will increase the contact resistance inside the electrode, thereby hindering the transmission of electrons inside the electrode, thereby reducing the electrolysis performance. Moreover, when the binder covers the surface of the membrane electrode, it will occupy a part of the active sites of the membrane electrode, thereby reducing the effective contact area between the catalyst and the electrolyte on the membrane electrode, thereby reducing the catalytic efficiency; secondly, the bonding force between the catalyst slurry and the release film is weak, which significantly affects the long-term service stability of the catalyst, and the catalyst is easy to fall off from the surface of the release film. Summary of the invention

[0004] The purpose of the present invention is to provide a method for in-situ preparing a single-atom electrocatalyst on the surface of a current collector, which can form catalyst active sites on the surface of the current collector through a reaction system during the preparation process, thereby improving the stability and catalytic efficiency of the catalyst.

[0005] To achieve the above object, the technical solution adopted by the present invention is: a method for preparing a single-atom electrocatalyst in situ on a current collector surface, comprising the following steps:

[0006] S1. The current collector is placed in acetone, hydrochloric acid and ethanol solutions for cleaning, and then dried naturally;

[0007] S2, preparing a metal salt solution, wherein the molar concentration of metal ions in the metal salt solution is between 0.0001 and 5 mol / L;

[0008] S3, preparing a dopamine hydrochloride solution and a tris(hydroxymethyl)aminomethane hydrochloride solution, then mixing the dopamine hydrochloride solution and the tris(hydroxymethyl)aminomethane hydrochloride solution to form a dopamine polymerization solution, and mixing the dopamine polymerization solution with the metal salt solution obtained in S2 to form a precursor solution, wherein the polydopamine in the dopamine polymerization solution combines with the metal ions in the metal salt solution through chelation to form polydopamine nanoparticles chelating the metal ions;

[0009] S4, placing the current collector obtained in S1 in the precursor solution obtained in S3, the characteristic groups on the surface of the polydopamine nanoparticles interact with the surface of the current collector to achieve in-situ pinning of the substrate, first heating the precursor solution to 20-40°C, keeping it warm and standing for 0.5-1h, then heating the precursor solution to 80-90°C, keeping it warm and standing for 0.5-1h, and finally heating the precursor solution to above 150°C for evaporation to obtain a catalyst rough blank;

[0010] S5. The catalyst rough billet obtained in S4 is annealed. During the annealing process, the annealing starting temperature is 200-300° C., and then heated to 700-1200° C. and maintained for 1-12 hours to obtain a single atom electrocatalyst.

[0011] Furthermore, in the aforementioned method for preparing a single-atom electrocatalyst in situ on the surface of a current collector, the current collector in S1 is any one of foam copper, foam nickel, foam titanium, foam cobalt, foam iron-nickel alloy, carbon cloth, carbon nanotube paper, carbon paper, and stainless steel mesh.

[0012] Furthermore, in the aforementioned method for preparing a single-atom electrocatalyst in situ on the surface of a current collector, when any corrosion-resistant material selected from foamed copper, foamed cobalt, foamed iron-nickel alloy, stainless steel mesh, carbon cloth, carbon nanotube paper, and carbon paper is used as the current collector, it is necessary to use hydrochloric acid with a molar concentration of 0.1 to 1 mol / L for cleaning, and when any corrosion-resistant material selected from foamed nickel and foamed titanium is used as the current collector, it is necessary to use hydrochloric acid with a molar concentration of 1 to 3 mol / L for cleaning.

[0013] Furthermore, the aforementioned method for preparing a single-atom electrocatalyst in situ on the surface of a current collector, wherein the metal salt solution in S2 is at least one of a nickel nitrate hexahydrate solution, a nickel chloride hexahydrate solution, a cobalt chloride hexahydrate solution, a cobalt nitrate hexahydrate solution, a ferric chloride solution, a ferric chloride solution, a zinc chloride solution, a zinc nitrate hexahydrate solution, a cupric chloride dihydrate solution, a cupric nitrate trihydrate solution, a manganese chloride tetrahydrate solution, a vanadium trichloride solution, a chloroiridic acid hydrate solution, a hydrated iridium trichloride solution, a hexachloroplatinic acid solution, a ruthenium chloride solution, and a rhodium chloride hydrate solution.

[0014] Furthermore, in the aforementioned method for preparing a single-atom electrocatalyst in situ on the surface of a current collector, the molar concentration of the dopamine hydrochloride solution in S3 is 0.001 to 1 mol / L, the molar concentration of the tris(hydroxymethyl)aminomethane hydrochloride solution is 0.001 to 2 mol / L, and the volume ratio between the dopamine hydrochloride solution and the tris(hydroxymethyl)aminomethane hydrochloride solution is 1:1.

[0015] Furthermore, in the aforementioned method for preparing a single-atom electrocatalyst in situ on the surface of a current collector, the volume ratio between the metal salt solution and the dopamine polymerization solution in S3 is 1:1-100.

[0016] Furthermore, in the aforementioned method for preparing a single-atom electrocatalyst in situ on the surface of a current collector, the annealing treatment atmosphere in S5 is any one of Ar gas, N2 gas, NH3 gas, and Ar / H2 mixed gas.

[0017] The advantages of the present invention are:

[0018] 1. The single-atom electrocatalyst prepared by the method of in-situ preparing the single-atom electrocatalyst on the surface of the current collector is distributed on the surface of the current collector. The current collector can provide a stable and conductive environment for the single-atom electrocatalyst, which is beneficial to improving the performance and stability of the single-atom electrocatalyst. The single-atom electrocatalyst is in-situ pinned to the surface of the current collector through a graphitized substrate, which can reduce the interface resistance between the single-atom electrocatalyst and the current collector, improve the electron transfer efficiency, and enhance the binding force between the single-atom electrocatalyst and the current collector, thereby preventing the single-atom electrocatalyst from falling off or deactivating during long-term use, and can significantly improve the long-term service stability of the single-atom electrocatalyst.

[0019] 2. Due to its unique structure, each metal ion of a single-atom electrocatalyst can become an active site, which greatly improves the atomic utilization efficiency and activity of the catalyst, so that the advantages of single-atom electrocatalysts can be fully utilized, so that single-atom electrocatalysts can more effectively promote the decomposition of water in the process of electrolysis of water to produce hydrogen, and achieve efficient electrolysis of water to produce hydrogen. At the same time, the components and content of single-atom electrocatalysts can be precisely controlled by regulating the molar concentration of metal salts, giving full play to the synergistic effect between multi-component single-atom electrocatalysts, and significantly optimizing their performance of electrolysis of water to produce hydrogen, which makes the in-situ preparation of single-atom electrocatalysts on the surface of the current collector have broad development prospects in the field of electrolysis of water to produce hydrogen. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The single-atom electrocatalyst prepared in Example 1 is 2 Overpotential diagram after a 500 h stability test cycle at 2 current density.

[0021] Figure 2 The single-atom electrocatalyst prepared in Example 2 is 2 Overpotential diagram after a 500 h stability test cycle at 2 current density.

[0022] Figure 3 The single-atom electrocatalyst prepared in Example 3 is 2 Overpotential diagram after a 500 h stability test cycle at 2 current density. DETAILED DESCRIPTION

[0023] The technical solution of the present invention is not limited to the specific implementation modes listed below, but also includes any combination of the specific implementation modes.

[0024] A method for preparing a single-atom electrocatalyst in situ on a current collector surface comprises the following steps:

[0025] S1. Place the current collector in acetone, hydrochloric acid, and ethanol solutions for cleaning, and then dry naturally; acetone can remove organic pollutants on the surface of the current collector, hydrochloric acid can remove metal oxides and other inorganic impurities on the surface of the current collector, and ethanol can remove residual acetone and hydrochloric acid, and can help the surface of the current collector to dry quickly. In this step, the current collector is any one of foam copper, foam nickel, foam titanium, foam cobalt, foam iron-nickel alloy, carbon cloth, carbon nanotube paper, carbon paper, and stainless steel mesh. When using any non-corrosion-resistant material of foam copper, foam cobalt, foam iron-nickel alloy, stainless steel mesh, carbon cloth, carbon nanotube paper, and carbon paper as the current collector, it is necessary to use hydrochloric acid with a molar concentration of 0.1 to 1 mol / L for cleaning. When using any corrosion-resistant material of corrosion-resistant foam nickel and foam titanium as the current collector, it is necessary to use hydrochloric acid with a molar concentration of 1 to 3 mol / L for cleaning, which can not only ensure the cleaning quality, but also prevent the structure from being corroded and damaged;

[0026] S2, prepare a metal salt solution; the metal salt solution is at least one of nickel nitrate hexahydrate solution, nickel chloride hexahydrate solution, cobalt chloride hexahydrate solution, cobalt nitrate hexahydrate solution, ferric chloride solution, ferric chloride solution, zinc chloride solution, zinc nitrate hexahydrate solution, cupric chloride dihydrate solution, cupric nitrate trihydrate solution, manganese chloride tetrahydrate solution, vanadium trichloride solution, chloroiridic acid hydrate solution, hydrated iridium trichloride solution, hexachloroplatinic acid solution, ruthenium chloride solution, and rhodium chloride hydrate solution, the molar concentration range of the metal salt solution is between 0.0001 and 5 mol / L, and the aggregation between metal ions can be reduced at a low molar concentration, so that each metal ion can be at an effective active site, which is more conducive to uniform dispersion on the substrate, thereby improving the selectivity and activity of the catalyst, and can accelerate the adsorption and dispersion of metal ions on the substrate at a high molar concentration, which helps to form a catalyst in a short time. A large number of active sites are formed to improve the catalytic efficiency. When the metal ions are distributed on the current collector, even if the amount of metal ions distributed on the surface of the current collector is small, the metal ions will form a sharp tip on the surface of the current collector, and the current collector itself is conductive, so when the current passes through the current collector, a tip discharge phenomenon will be formed at this tip, increasing the discharge amount at this position, thereby improving the catalytic effect. When selecting the molar concentration of the metal salt solution, it is necessary to select according to the actual product usage requirements. If it is on civilian or low-cost equipment, a metal salt solution with a lower molar concentration of metal ions can be configured. If it is on high-precision equipment, a metal salt solution with a higher molar concentration of metal ions needs to be configured. High molar concentration metal ions will interfere with each other due to excessive reaction potential, thereby affecting the reaction efficiency. Therefore, the molar concentration range of the metal salt is controlled between: 0.0001 and 5 mol / L;

[0027] S3, first prepare dopamine hydrochloride solution and tris(hydroxymethylaminomethane) hydrochloride solution, the molar concentration of dopamine hydrochloride solution is 0.001-1 mol / L, the molar concentration of tris(hydroxymethylaminomethane) hydrochloride solution is 0.001-2 mol / L, then mix the dopamine hydrochloride solution and tris(hydroxymethylaminomethane) hydrochloride solution to form a dopamine polymerization solution, the volume ratio between the dopamine hydrochloride solution and the tris(hydroxymethylaminomethane) hydrochloride solution is 1:1, the tris(hydroxymethylaminomethane) hydrochloride solution can provide weak alkaline conditions, so that the dopamine hydrochloride in the dopamine hydrochloride solution is in the weak alkaline conditions. Under the conditions, a self-polymerization reaction is easily generated to form polydopamine, which is mixed with the metal salt solution obtained in S2 to form a precursor solution, wherein the volume ratio between the metal salt solution and the dopamine polymerization solution is 1:1-100, and polydopamine is combined with metal ions in the metal salt solution through chelation to form polydopamine nanoparticles chelated with metal ions. This chelation not only improves the stability of metal ions, but also the metal ions coordinate with polydopamine to form coordination compounds, and this coordination will change the electronic structure of metal ions, thereby affecting their catalytic activity and selectivity;

[0028] S4. The current collector obtained in S1 is placed in the precursor solution obtained in S3. The characteristic groups on the surface of the polydopamine nanoparticles interact with the surface of the current collector to achieve in-situ pinning of the substrate. In addition, polydopamine has good adhesion and biocompatibility, and can modify the surface of the current collector to improve the adhesion, corrosion resistance and biocompatibility of the current collector, thereby improving the adhesion strength between the metal ions and the current collector. Polydopamine can form a uniform polydopamine coating on the surface of the current collector. This coating not only increases the surface area and pore structure of the current collector, but also enhances its conductivity and electrochemical stability. During the standing process, the precursor solution is first uniformly heated to 20-40°C and kept at this temperature for 0.5-1h. Then the precursor solution is uniformly heated to 80-90°C and kept at this temperature for 0.5-1h. Then The precursor solution is uniformly heated to above 150°C, and a catalyst rough blank is obtained after the precursor solution is evaporated. The reaction rate between the metal ions and the current collector is slow at a lower temperature. As the solution temperature increases, the reaction rate will gradually accelerate. The precursor solution is first heated to a low temperature of 20 to 40°C to avoid the metal ions from agglomerating and being unable to be evenly distributed on the current collector due to too fast a heating rate or too high a temperature. Keeping it warm and standing for 0.5 to 1 hour can play a curing role, so that the metal ions adapt to the temperature, and then heating it to 80 to 90°C to accelerate the deposition of the metal ions. The precursor solution begins to evaporate in a non-boiling state, accelerating the reaction between the metal ions and the current collector within a controllable range. After keeping it warm and standing for 0.5 to 1 hour, when most of the metal ions are distributed on the current collector, the precursor solution is heated to above 150°C to evaporate the precursor solution quickly;

[0029] S5. Annealing the catalyst rough billet obtained in S4, with the annealing starting temperature being 200-300°C, and then heating to 700-1200°C and maintaining for 1-12 hours to obtain a single-atom electrocatalyst. The mixed solution of hydroxymethylaminomethane hydrochloride and dopamine hydrochloride will be coated on the catalyst rough billet to form a film after the heating evaporation treatment in S3, which affects the flow of electrons and thus the catalytic effect. After high-temperature annealing, hydroxymethylaminomethane hydrochloride and dopamine hydrochloride can be graphitized, and the graphitized structure can enable electrons to flow to ensure the catalytic effect. The annealing atmosphere is any one of Ar gas, N2 gas, NH3 gas, and Ar / H2 mixed gas.

[0030] The single-atom electrocatalyst prepared by the method of in situ preparing single-atom electrocatalysts on the surface of a current collector is distributed on the surface of the current collector. The current collector can provide a stable and conductive environment for the single-atom electrocatalyst, which is beneficial to improving the performance and stability of the single-atom electrocatalyst. The single-atom electrocatalyst is in situ pinned to the surface of the current collector through a graphitized substrate, which can reduce the interface resistance between the single-atom electrocatalyst and the current collector, improve the electron transfer efficiency, and enhance the binding force between the single-atom electrocatalyst and the current collector, thereby preventing the single-atom electrocatalyst from falling off or deactivating during long-term use, and can significantly improve the long-term service stability of the single-atom electrocatalyst.

[0031] Due to its unique structure, each metal ion of a single-atom electrocatalyst can become an active site, which greatly improves the atomic utilization efficiency and activity of the catalyst. The advantages of single-atom electrocatalysts can be fully utilized, so that single-atom electrocatalysts can more effectively promote the decomposition of water in the process of electrolysis of water to produce hydrogen, and achieve efficient electrolysis of water to produce hydrogen. At the same time, the components and content of single-atom electrocatalysts can be precisely controlled by regulating the molar concentration of metal salts, giving full play to the synergistic effect between multi-component single-atom electrocatalysts, and significantly optimizing their performance of electrolysis of water to produce hydrogen. This makes the in-situ preparation of single-atom electrocatalysts on the surface of the current collector have broad development prospects in the field of electrolysis of water to produce hydrogen.

[0032] Embodiment 1

[0033] The current collector in step S1 is carbon nanotube paper. Carbon nanotube paper has high conductivity and can establish multiple electron pathways to the electrodes, making the electron transmission of the battery more efficient during the charging and discharging process, reducing resistance and energy loss. The porous structure of carbon nanotube paper effectively enhances the adhesion of metal ions, helps metal ions to better adhere to the current collector and reduce the risk of falling off. When cleaning the carbon nanotube paper, hydrochloric acid with a molar concentration of 0.1 mol / L is selected, which can not only achieve effective cleaning but also prevent the carbon nanotube paper from being corroded and damaged.

[0034] The metal salt solution in step S2 is mixed with nickel nitrate hexahydrate solution, chloroiridic acid hydrate solution, ruthenium chloride solution and rhodium chloride hydrate solution, and the total molar concentration of metal ions in the metal salt solution is 0.0004 mol / L, wherein the molar concentration of nickel nitrate hexahydrate solution is 0.0001 mol / L, the molar concentration of chloroiridic acid hydrate solution is 0.0001 mol / L, the molar concentration of ruthenium chloride solution is 0.0001 mol / L, and the molar concentration of rhodium chloride hydrate solution is 0.0001 mol / L. L, the metal ions in these metal salt solutions undergo a reduction reaction on the surface of the current collector to form a metal coating, which can significantly improve the conductivity of the current collector. For example, the coating formed on the surface of the current collector by the metal ions in the nickel nitrate hexahydrate solution also has a certain corrosion resistance, which can protect the current collector from corrosion by the electrolyte solution and extend the service life of the electrochemical device. Precious metal salt solutions such as ruthenium chloride solution and rhodium chloride hydrate solution can form a metal coating with specific functions on the surface of the current collector, such as improving wear resistance and improving optical properties.

[0035] The molar concentration of the dopamine hydrochloride solution in step S3 is 0.001 mol / L, the molar concentration of the tris(hydroxymethyl)aminomethane hydrochloride) solution is 0.001 mol / L, the volume ratio between the dopamine hydrochloride solution and the tris(hydroxymethyl)aminomethane hydrochloride) solution in the dopamine polymerization solution is 1:1, and the volume ratio between the metal salt solution and the dopamine polymerization solution is 1:20.

[0036] In step S4, the mixture is first heated to 30° C., kept at this temperature and allowed to stand for 50 min, then heated to 80° C., kept at this temperature and allowed to stand for 50 min, and finally heated to 150° C. for rapid evaporation.

[0037] The annealing atmosphere in step S5 is N2, the annealing temperature is 750° C., and the annealing time is 6 hours.

[0038] from Figure 1 It can be seen that the overpotential of the single-atom electrocatalyst prepared by this embodiment under the test conditions of 0h, 100h, and 500h for total water decomposition is only 1.56V, 1.57V, and 1.58V, and the atomic electrocatalyst can still maintain a low overpotential after long-term use, indicating that the in-situ prepared single-atom electrocatalyst obtained by the method of the present invention has a good long-term service life.

[0039] Embodiment 2

[0040] The current collector in step S1 is titanium foam. When cleaning the titanium foam, hydrochloric acid with a molar concentration of 1 mol / L is selected to achieve effective cleaning.

[0041] The metal salt solution in step S2 is composed of a chloroiridic acid hydrate solution and a rhodium chloride hydrate solution, and the total molar concentration of metal ions in the metal salt solution is 0.0004 mol / L, wherein the molar concentration of the chloroiridic acid hydrate solution is 0.0002 mol / L, and the molar concentration of the rhodium chloride hydrate solution is 0.0002 mol / L.

[0042] The molar concentration of the dopamine hydrochloride solution in step S3 is 0.001 mol / L, the molar concentration of the tris(hydroxymethyl)aminomethane hydrochloride) solution is 0.001 mol / L, the volume ratio between the dopamine hydrochloride solution and the tris(hydroxymethyl)aminomethane hydrochloride) solution in the dopamine polymerization solution is 1:1, and the volume ratio between the metal salt solution and the dopamine polymerization solution is 1:50.

[0043] In step S4, the mixture is first heated to 40° C., kept at this temperature and allowed to stand for 30 minutes, then heated to 90° C., kept at this temperature and allowed to stand for 30 minutes, and finally heated to 150° C. for rapid evaporation.

[0044] The annealing atmosphere in step S5 is NH 3 , the annealing temperature is 900° C., and the annealing time is 1 h.

[0045] from Figure 2 It can be seen that the overpotential of the single-atom electrocatalyst prepared by this embodiment for total water decomposition under the test conditions of 0h, 100h, and 500h is only 1.70V, 1.72V, and 1.73V. The atomic electrocatalyst can still maintain a low overpotential after long-term use, indicating that the in-situ prepared single-atom electrocatalyst obtained by the method of the present invention has a good long-term service life.

[0046] Embodiment 3

[0047] The current collector in step S1 is a foamed iron-nickel alloy. When cleaning the foamed iron-nickel alloy, hydrochloric acid with a molar concentration of less than 1 mol / L is selected.

[0048] The metal salt solution in step S2 is composed of a chloroiridic acid hydrate solution, a ruthenium chloride solution, and a rhodium chloride hydrate solution, and the total molar concentration of metal ions in the metal salt solution is 0.0005 mol / L, wherein the molar concentration of the chloroiridic acid hydrate solution is 0.0001 mol / L, the molar concentration of the ruthenium chloride solution is 0.0001 mol / L, and the molar concentration of the rhodium chloride hydrate solution is 0.0003 mol / L.

[0049] In step S4, the mixture is first heated to 20° C., kept at this temperature and allowed to stand for 1 hour, then heated to 80° C., kept at this temperature and allowed to stand for 1 hour, and finally heated to 150° C. for rapid evaporation.

[0050] The annealing atmosphere in step S5 is N2, the annealing temperature is 1100° C., and the annealing time is 2 h.

[0051] from Figure 3 It can be seen that the overpotential of the single-atom electrocatalyst prepared by this embodiment under the test conditions of 0h, 100h, and 500h for total water decomposition is only 1.63V, 1.66V, and 1.68V. The single-atom electrocatalyst can still maintain a low overpotential after long-term use, indicating that the in-situ prepared single-atom electrocatalyst obtained by the method of the present invention has a good long-term service life.

[0052] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present invention can still be modified or replaced by equivalents. Any modification or equivalent replacement that does not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a single-atom electrocatalyst in situ on a current collector surface, characterized in that: The following steps are involved: S1. The current collector is placed in acetone, hydrochloric acid and ethanol solutions for cleaning, and then dried naturally; S2, preparing a metal salt solution, wherein the molar concentration of metal ions in the metal salt solution is between 0.0001 and 5 mol / L; S3, preparing a dopamine hydrochloride solution and a tris(hydroxymethyl)aminomethane hydrochloride solution, then mixing the dopamine hydrochloride solution and the tris(hydroxymethyl)aminomethane hydrochloride solution to form a dopamine polymerization solution, and mixing the dopamine polymerization solution with the metal salt solution obtained in S2 to form a precursor solution, wherein the polydopamine in the dopamine polymerization solution combines with the metal ions in the metal salt solution through chelation to form polydopamine nanoparticles chelating the metal ions; S4, placing the current collector obtained in S1 in the precursor solution obtained in S3, the characteristic groups on the surface of the polydopamine nanoparticles interact with the surface of the current collector to achieve in-situ pinning of the substrate, first heating the precursor solution to 20-40°C, keeping it warm and standing for 0.5-1h, then heating the precursor solution to 80-90°C, keeping it warm and standing for 0.5-1h, and finally heating the precursor solution to above 150°C for evaporation to obtain a catalyst rough blank; S5. The catalyst rough billet obtained in S4 is annealed. During the annealing process, the annealing starting temperature is 200-300° C., and then heated to 700-1200° C. and maintained for 1-12 hours to obtain a single atom electrocatalyst.

2. The method for preparing a single-atom electrocatalyst in situ on a current collector surface according to claim 1, characterized in that: The current collector in S1 is any one of foam copper, foam nickel, foam titanium, foam cobalt, foam iron-nickel alloy, carbon cloth, carbon nanotube paper, carbon paper, and stainless steel mesh.

3. The method for preparing a single-atom electrocatalyst in situ on a current collector surface according to claim 2, characterized in that: When using any corrosion-resistant material such as foam copper, foam cobalt, foam iron-nickel alloy, stainless steel mesh, carbon cloth, carbon nanotube paper, and carbon paper as the current collector, it is necessary to use hydrochloric acid with a molar concentration of 0.1 to 1 mol / L for cleaning. When using any corrosion-resistant material such as foam nickel or foam titanium as the current collector, it is necessary to use hydrochloric acid with a molar concentration of 1 to 3 mol / L for cleaning.

4. The method for preparing a single-atom electrocatalyst in situ on a current collector surface according to claim 1, characterized in that: The metal salt solution in S2 is at least one of nickel nitrate hexahydrate solution, nickel chloride hexahydrate solution, cobalt chloride hexahydrate solution, cobalt nitrate hexahydrate solution, ferric chloride solution, ferric chloride solution, zinc chloride solution, zinc nitrate hexahydrate solution, cupric chloride dihydrate solution, cupric nitrate trihydrate solution, manganese chloride tetrahydrate solution, vanadium trichloride solution, chloroiridic acid hydrate solution, hydrated iridium trichloride solution, hexachloroplatinic acid solution, ruthenium chloride solution, and rhodium chloride hydrate solution.

5. The method for preparing a single-atom electrocatalyst in situ on a current collector surface according to claim 1, characterized in that: The molar concentration of the dopamine hydrochloride solution in S3 is 0.001-1 mol / L, the molar concentration of the tris(hydroxymethyl)aminomethane hydrochloride solution is 0.001-2 mol / L, and the volume ratio between the dopamine hydrochloride solution and the tris(hydroxymethyl)aminomethane hydrochloride solution is 1:

1.

6. The method for preparing a single-atom electrocatalyst in situ on a current collector surface according to claim 5, characterized in that: The volume ratio between the metal salt solution and the dopamine polymerization solution in S3 is 1:1-100.

7. The method for preparing a single-atom electrocatalyst in situ on a current collector surface according to claim 1, characterized in that: The annealing treatment atmosphere in S5 is any one of Ar gas, N2 gas, NH3 gas, and Ar / H2 mixed gas.